WMAP and the generalized Chaplygin gas - Amendola, Luca (Journal of cosmology and astroparticle physics, 2003)
We compare the WMAP temperature power spectrum and SNIa data to models with a generalized Chaplygin gas as dark energy. The generalized Chaplygin gas is a component with an exotic equation of state, p X = − A /ρ α X (a polytropic gas with negative constant and exponent). Our main result is that, restricting to a flat universe and to adiabatic pressure perturbations for the generalized Chaplygin gas, the constraints at 95% CL to the present equation of state w X = p X /ρ X and to the parameter α are−1 ≤ w X < −0.8, 0 ≤ α < 0.2, respectively. Moreover, we show that a Chaplygin gas (α = 1) is ruled out as a candidate for dark energy by our analysis at more than the 99.99% CL. A generalized Chaplygin gas appears much less likely as a unified dark matter candidate (Ω CDM = 0) than as a dark energy model, although its χ 2 is only two sigma away from the expected value.